Is Chemistry everything to Engineering Students? Let their experiences talk - Khoza, Simon Bheki (South African Journal of Higher Education, 2016)
This article draws on a case study of five engineering students who were studying Chemistry at a university in South Africa. Chemistry was one of the compulsory modules as it was claimed to be everything to engineering students but indicated also as one of the most difficult modules because it has many concepts. This article gives these students a voice by investigating their experiences framed by the Curricula Spider Web. The experiences of students tell different stories around the claim. Data generation occurred through document analysis and one-to-one semi-structured interviews. This article prioritises the alignment of Technology in Education (hard-ware and soft-ware) and Technology of Education (ideological-ware) in order to do justice to engineering students. This study is important because it may contribute towards finding a solution around the high failure rate of students in learning Chemistry.